1987
DOI: 10.1073/pnas.84.11.3565
|View full text |Cite
|
Sign up to set email alerts
|

Heparin sequences in the heparan sulfate chains of an endothelial cell proteoglycan.

Abstract: The structure of the glycosaminoglycan chain of a heparan sulfate proteoglycan isolated from the conditioned medium of an endothelial cell line has been analyzed by using various degradative enzymes (heparitinase I, heparitinase II, heparinase, glycuronidase, sulfatases) from Flavobacterium heparinum. This proteoglycan inhibits the thromboplastinactivated pathway of coagulation; as a consequence, the catalytic conversion of prothrombin to thrombin is arrested. Heparitinase I (EC 4.2.2.8), an enzyme with specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 20 publications
4
88
0
1
Order By: Relevance
“…The results obtained with trachea heparan sulfate imply that the iduronic acid residues are located in different regions along the molecule; this pattern of distribution differs from known standards. The same type of profile of heparinase products was found previously in rabbit aorta endothelial cells (36). DISCUSSION We have unexpectedly found in cells from a tissue that does not synthesize heparin a very abundant message encoding a protein that has 95% sequence identity with the putative heparin N-acetylglucosaminyl N-deacetylase/N-sulfotransferase.…”
Section: Structure Of Heparan Sulfate Synthesized By CCL 44supporting
confidence: 83%
“…The results obtained with trachea heparan sulfate imply that the iduronic acid residues are located in different regions along the molecule; this pattern of distribution differs from known standards. The same type of profile of heparinase products was found previously in rabbit aorta endothelial cells (36). DISCUSSION We have unexpectedly found in cells from a tissue that does not synthesize heparin a very abundant message encoding a protein that has 95% sequence identity with the putative heparin N-acetylglucosaminyl N-deacetylase/N-sulfotransferase.…”
Section: Structure Of Heparan Sulfate Synthesized By CCL 44supporting
confidence: 83%
“…In fact, a recent study demonstrates heparin sequences in the heparan sulfate chains of an endothelial cell proteoglycan. 189 Anticoagulant HS has been isolated from vascular tissue that was shown to be free of mast cells. 38 However, Imamura and Mitsui 190 recently demonstrated that heparan sulfate and heparin exhibited opposing activities on the growth of human umbilical vein endothelial cells in the presence of acidic and basic FGF.…”
mentioning
confidence: 99%
“…Endogenous (30) and by enzymatic digestion with chondroitinase ABC (Sigma) and heparitinases I and II (31).…”
Section: Methodsmentioning
confidence: 99%
“…After electrophoresis heparan sulfate was precipitated in the gel with 0.1% cetyltrimethyl ammonium bromide (Sigma). The dried gel was stained with 0.1% toluidine blue as described to visualize the heparan sulfate, and the radioactive heparan sulfate was detected by autoradiography (30).…”
Section: Methodsmentioning
confidence: 99%